MODEL COMPLEMENT AND FOCUS DALAM PENANGANAN PASCA BENCANA TAHAP REHABILITASI (Studi Kasus pada Peristiwa Gempa Bumi di Klaten, 27 Mei 2006) - Qomarun, Qomarun (Universitas Muhammadiyah Surakarta, 2007)
The objective of this model is to cover the interest of both donorand acceptor of aid in the event of post disaster. The complement andfocus model is being developed in the fact of their condition which isalmost the same. Complement model is conducted by sharing power, whilefocus model is conducted by centralization of scope. To approach theobjective, the activities are conducted by design and build pattern. Afterwards,the try and errormodelshould be developed to coverboth thelackofliteratureand the speed of changing. In this case study,we found the newactivitywhich was called demolition programin handling post earthquakedisaster.The main activity of that programis destroyingand cleaningthebuilt environmentwhich is almost collapse. Actually,this activity isreallyhelpful for some people in the field, although we have yet to design.